Net Working Capital versus Net Owner's Equity Approaches to Computing Zakatable Amount: A Conceptual Comparison and Application (American Journal of Islam and Society, 1992)
IntroductionZakah is a form of tax and alms mandated by Islam? The concepts underlyingzakah are that the rich are responsible for the poor and the poor havethe right to receive zakah. This does not imply that Islam is anticapitalist;in fact, Islam motivates the rich to invest funds so they will not be diminshedby paying zakah. Islam opposes idle savings, as it encourages the investmentof funds for increased production, employment, and assistance to the poor.~Zakah is ordained by the Qur'an, but its technical details are interpreted bythe rules and jurisprudence of Islam.All economic entities maintain financial records of some kind and preparefinancial statements according to generally accepted accounting standards.These records and statements are designed for different purposes and arenot necessary for determining the amount of wealth subject to zakah. Manyresearchers have investigated the methods employed to determine the zakatableamount levied on trade assets ('Urud al tijarah). These methods may be summarizedinto two approaches: a) the net working capital approach and b)the owner's equity approach.This paper investigates the feasibility of using the net working capitalapproach (i.e., accounting principles) and the owner's net equity approach(i.e., the Saudi system) to determine the zakatable amount of trade assets.It will also show the relationship between the two approaches.This paper is divided into five sections: a) introducing the principlesand conditions of zakah accounting for businesses; b) discussing the net workingcapital approach and how to determine the growing capital as the basisfor ascertaining the &table amount by analyzing the elements of workingcapital and the financial transactions during the year; c) analyzing the owner'sequity approach used in Saudi Arabia to determine the &table amount;d) applying both approaches to a numerical example; and e) contrasting thegrowing capital with the zakatable amount.Principles and Conditions of Trade Zakah('Urud al Tijarah)There are two types of assets. The first type, which is not subject tozakah, includes those capital assets owned for the purpose of using themin one's business. Examples of such assets are the tools and machines usedfor production or marketing. The second type, which is subject to zakah,includes those assets manufactured or purchased for malung a profit by resellingthem ...